The Effects of Aerobic Training and Age on Plasma sICAM-1 - Many, G. M.; Jenkins, N. T.; Witkowski, S.; Damsker, J. M.; Hagberg, J. (International Journal of Sports Medicine, 2013)
Chronic low-grade systemic inflammation plays a role in the development of cardiovascular (CV) disease. Habitual endurance exercise training reduces the risk of CV disease in part through anti-inflammatory mechanisms. The purpose of this study was to investigate the effects of age, endurance training status, and their interaction on pro-inflammatory plasma cytokines involved in the pathogenesis of CV disease. Subjects were BMI-matched young (25±3 years; endurance trained: n=9, sedentary: n=11) and older (62±5 years; endurance-trained: n=12, sedentary: n=11) men. Plasma cytokine concentrations were determined by multiplex cytometric bead assay. Soluble intercellular adhesion molecule-1 (sICAM-1) levels were 40% higher in sedentary older men compared to young sedentary subjects (P=0.048), but they were not different between the young and older trained men. Furthermore, sICAM-1 levels were negatively correlated with maximal oxygen uptake (V˙O2max; r= − 0.38, P=0.01) across all subjects. There were no significant differences among the groups in plasma concentrations of monocyte chemoattractant protein-1 (MCP-1), soluble tumor necrosis-α receptor (sTNFR), soluble CD40 ligand (sCD40L), or resistin. We conclude that habitual endurance training is associated with an attenuated age-related increase in plasma sICAM-1.
Keywords: systemic inflammation; age; endurance training; physical inactivity; adhesion molecules